2022
DOI: 10.1136/bmjgh-2021-007666
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 lockdowns on adolescent pregnancy and school dropout among secondary schoolgirls in Kenya

Abstract: IntroductionSecondary school closures aimed at limiting the number of infections and deaths due to COVID-19 may have amplified the negative sexual and reproductive health (SRH) and schooling outcomes of vulnerable adolescent girls. This study aimed to measure pandemic-related effects on adolescent pregnancy and school dropout among school-going girls in Kenya.MethodsWe report longitudinal findings of 910 girls in their last 2 years of secondary school. The study took place in 12 secondary day schools in rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 35 publications
1
74
0
Order By: Relevance
“…Moreover, a Nigerian study found that dropout increased with age, and noted stronger effects for girls in a region with higher child marriage rates ( Dessy et al, 2021 ). Similarly, the Kenyan study that documented increased pregnancy and dropout focused on female students in their last two years of secondary school ( Zulaika et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a Nigerian study found that dropout increased with age, and noted stronger effects for girls in a region with higher child marriage rates ( Dessy et al, 2021 ). Similarly, the Kenyan study that documented increased pregnancy and dropout focused on female students in their last two years of secondary school ( Zulaika et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study compared girls who were expected to complete secondary school just before the pandemic (2019) to those expected to complete schooling just after the pandemic (2021). They found that Kenyan girls who experienced COVID-19 closures were twice as likely to report a pregnancy and three times as likely to dropout ( Zulaika et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…21 Across low and middle income countries, including India, there has been a growing number of programs and interventions targeting these perceptions and attitudes in an effort to improve health and educational outcomes during and after adolescence. 10,12,16,20 Investing in building positive and equitable gender attitudes, and growing voice, agency, self-efficacy and locus of control are key mechanisms to ensuring that adolescents eventually become educated, healthy, and prosperous adults. 9,23,24 The findings of this study are especially useful as the world moves out of the peak and deadliest phase of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…15 In a recent study conducted by Zulaika et al adolescent girls in Kenya who remained out of school for longer than six months due to the COVID-19 outbreak, twice as likely to become pregnant and three times as likely to drop out of school than those girls that graduated prior to 2020. 16 While it may take many years, and many studies to fully understand the sequelae of the COVID-19 pandemic in India (and around the world), prior research shows a consistent link to the pandemic and inequalities when it comes to girls and women. It is evident that experiences from pandemics and large-scale crises often affect men and women differently.…”
mentioning
confidence: 99%
“…In Malawi, for instance, an 11% increase in teenage pregnancies was recorded from January to August 2020 compared to the same period in 2019 (UNFPA, 2021). Scientific studies document a dramatic rise in the risk of young girls becoming pregnant, for instance, in Kenya (Zulaika et al, 2022), Nigeria (Musa et al, 2021) and other African countries (see the review by Willie, 2021).…”
Section: Additional Effect Of Increases In Teenage Pregnancy On Girls...mentioning
confidence: 99%